World sustainable development outlook 2007 : knowledge management and sustainable development in the 21st century - Ahmed, A. (Allam) (Greenleaf, 2007)
Adopting a holistic approach, this book critically examines the interrelationship between knowledge management, developing countries and sustainable development. Taking into account a variety of international, institutional and intellectual perspectives, it uses case and country studies to highlight successful initiatives, ideas and innovations.